Agronomic Characterization of Three Local Krai Cucumber Accessions for the Selection of Potential Accessions - Nanda Firdaus Syafe`i Putro; Sari Megawati; Elea Nur Aziza (PAKIS JOURNAL INSTITUTE, 2026)
Local krai cucumber (Cucumis sativus L.) accessions represent valuable genetic resources for the development of cultivars with desirable agronomic and fruit characteristics. This study aimed to determine the agronomic characteristics of three local krai cucumber accessions as a basis for selecting potential accessions. The study was conducted from December 2025 to March 2026 at the Karangsari experimental field, Sleman, Yogyakarta, at an altitude of approximately 200 m above sea level. The study used a one-factor randomized complete block design (RCBD), consisting of three local krai cucumber accessions, namely CBT-246 Lamongan, CBT-248 Sidoarjo, and CBT-267 Rembang, with six replications. The observed parameters included fruit weight per plant, number of fruits per plant, fruit weight per plot, number of fruits per plot, fruit length, fruit diameter, leaf blade length, leaf blade width, flowering time, and first harvest time. Data were analyzed using ANOVA at the 5% significance level, followed by Tukey’s HSD test at α = 0.05. The results showed that the three accessions differed significantly in fruit weight per plant, fruit length, fruit diameter, leaf blade width, and flowering time. Accession CBT-267 Rembang showed superior performance in the highest fruit weight per plant, reaching 841.72 g, the greatest fruit length, reaching 39.42 cm, and the earliest flowering time, at 22.00 days after planting (DAP). Meanwhile, CBT-246 Lamongan had the largest average fruit diameter, at 5.78 cm, and the widest leaf blade, at 17.90 cm. Based on these results, CBT-267 Rembang has potential as a promising accession for the selection of long-fruited types with high fruit weight per plant. However, further multilocation and multiseason trials are required to confirm the stability of its agronomic characteristics.